HOMOSEXUALITY IN ANDRE ACIMAN’S CALL ME BY YOUR NAME - Ari Windriani; Tri Pramesti (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
This study discusses about Elio’s homosexuality in Andr? Aciman’s Call Me by Your Name. Elio is the main character in the novel. The study aims to answer three points: the cause of Elio’s homosexuality, the effect of Elio’s homosexuality and how homosexuality presented in the novel. The study uses qualitative research because it provides understanding into the problem and it derives meanings from the quotations. This study applies intrinsic and extrinsic approaches. The extrinsic approach used is psychological approach as the literary approach. The psychological approach is applied in causes and effects of homosexuality as a psychological issue. The data source of this study is Call Me by Your Name novel by Andr? Aciman. The study found that Elio’s homosexuality is caused by Elio’s hormone and Elio’s family life. Elio’s desire and lust brings him to the wild imagination and fantasy. Elio’s parents are open-minded. It can be concluded that from the causes of Elio’s homosexuality brings him to the taboo thing and not every people can accept that sexual orientation. The novelist, Andr? Aciman wants to presented about the true feeling of the taboo love.